Hubungan Pendidikan Kepramukaan dengan Prestasi Belajar Anggota Pramuka Universitas Negeri Makassar - Muthahara Yulina; Haripuddin Haripuddin; Lu'mu Lu'mu (Universitas Negeri Makassar, 2023)
This study discusses the application of students' positive character values in class as a manifestation of the results of their character education in Scouting. The aim is to find out the learning process of scout members, the level of learning achievement, and the relationship between scouting education and learning achievement of Scout members at Makassar State University. This research includes correlation research with a quantitative approach which is described descriptively. Methods of data collection using interviews, documentation and questionnaires. The population in this study were seventy respondents (Scouting members). The data analysis technique used is product moment correlation analysis and simple linear regression using the Statistical Package for Social Sciences (SPSS) program. The results showed that the majority of respondents often applied the six characters studied in the learning process in class with a total recapitulation of respondents' answers on the scouting education variable of eighty point thirty four percent. In addition, the level of academic achievement is classified as very high, namely eighty-nine point twenty-one percent. The correlation between the variable scouting education and learning achievement is zero point five hundred and sixty five so that the range of Pearson correlation values for the two variables is in the moderate correlation. In this study it can be concluded that scouting education has a positive and significant relationship to the learning achievement of Scout members at Makassar State University where if scouting education increases by one percent, then learning achievement will increase by one point eight hundred and eighty percent.